Simulation on Parameter and Characteristics Extraction Between Two Simulation Packages (Synopsys and PSpice) - Nor Aznin Sakrani (Universiti Malaysia Perlis, 2008)
The progress of silicon technologies in the last twenty years has traced the path to the unprecedented revolution of information technologies, which has changed everybody’s lifestyles. Apparently, this has happened with the help from TCAD tools. In this project, Synopsys Taurus Workbench including TSUPREM-4 and Medici is used as a virtual IC factory that simulates semiconductor manufacturing processes and predicts device characteristics. PSpice TCAD tool is used afterwards for circuit simulation. The objective is of this project is to match these two program packages in the area of parameter and characteristics extraction. First, an initial device of NMOS of gate length of 1.5μm with different values of substrate concentration and gate oxide thickness is created by using TSUPREM-4 from Synopsys. The extraction of the parameter and electrical characteristics is then carried out in Medici. Next, using PSpice TCAD tool, the circuit level for NMOS is designed and electrical characteristics are obtained. The parameter of interest to be extracted is the threshold voltage Vth. The results obtained from these two simulation packages are then compared and its percentage of different is analyzed. For dopant concentration of boron B=1015atoms/cm3 the percentage of different of Vth for the varied gate oxide thickness Tox is between 2.45% until 12.49%, while for NB=1018atoms/cm3 percentage of different of Vth is between 0.15% until 3.04%. The results show that the average percentage of different for dopant concentration NB=1015atoms/cm3 is higher than the average percentage of different for dopant concentration NB=1018atoms/cm3. Generally, the electrical characteristics and parameters can be extracted from these two simulation packages-Synopsys and PSpice, and both can be accepted as the design tools for integrated circuits.